Role of Fathers in Children’s Education from the Qur’an Perspective and Its Relevance to Developmental Psychology Concepts - Al Arifi, Nasiruddin; Malihah, Noor; Fauzan, Umar (UIN Sultan Aji Muhammad Idris Samarinda, 2023)
This research is motivated by the phenomenon of misperception regarding the currently minimal role of fathers in children's education. This research aims to explore more deeply the views of the Koran regarding the role of fathers in children's education through dialogue media and its relevance to the concept of developmental psychology. This library research study uses a thematic approach with documentation techniques for data collection which is then analyzed using content analysis techniques. There are fourteen verses containing dialogue between father and son with a typical approach style including: 1) dialogue, 2) positive advice, 3) role modeling, 4) mentoring, 5) discussion partner and 6) giving trust in the form of delegation. The results of research based on the found verses show that the Qur'an provides a clear picture of the importance of the active role of fathers in children's education. Not only physical presence but also character presence and direct verbal guidance in order to become a role model, guide and discussion partner according to the child's age level. This is in line with the concept of developmental psychology which states that the masculine characteristics of fathers as role models and mentors are needed to complete a child's development to the optimal stage.